ANT 2008/09: AWI airborne Radio-Echo Sounding data over eastern Dronning Maund Land and East Antarctica and Berkner Island (RBI and WEGAS Projects) - Olaf Eisen; Wilfried Jokat; Daniel Steinhage; Veit Helm; Richard C A Hindmarsh (PANGAEA, 2025)
This dataset contains airborne radar data acquired using the AWI EMR system during the Antarctic season of 2008/09. The profiles extend across the eastern Dronning Maud Land , the ice shelfes and Berkner Island. The data are available as netCDF files (including waveforms and metadata), KML files of the profile line locations, and quicklook images of the radargrams.